Exploring Information Available to and Used by Physicians on Antibiotic Use and Antibiotic Resistance in Jordan - Reema A. Karasneh; Sayer I. Al-Azzam; Mera A. Ababneh; Iman A. Basheti; Ola Al-Azzeh; Sarah Al Sharie; Barbara R. Conway; Mamoon A. Aldeyab (Antibiotics, 2021)
Evidence based information sources for physicians are needed for informed antibiotic prescribing practices. The aim of this study was to explore physicians’ preferred sources of information and evaluate physicians’ awareness of available information and initiatives on prudent antibiotic prescribing in Jordan. A cross-sectional study was conducted utilizing an online questionnaire and included physicians (n = 409) from all sectors and specialties in Jordan. Published guidelines (31.8%), the workplace (25.7%), colleagues or peers (20.0%), group or conference training (18.3%), and the medical professional body (18.1%) were the main sources of information about avoiding unnecessary antibiotic prescribing, with the influence of these sources on changing prescribers’ views being 34.7%, 17.1%, 11%, 13.4%, and 7.6%, respectively. One-third of physicians (33.7%) reported no knowledge of any initiatives on antibiotic awareness and resistance. Regarding awareness of national action plans on antimicrobial resistance, 10.5%, 34%, and 55.5% of physicians were aware, unaware, and unsure of the presence of any national action plans, respectively. Physicians showed interest in receiving more information on resistance to antibiotics (58.9%), how to use antibiotics (42.2%), medical conditions for which antibiotics are used (41.3%), prescribing of antibiotics (35.2%), and links between the health of humans, animals, and the environment (19.8%). The findings can inform interventions needed to design effective antimicrobial stewardship, enabling physicians to prescribe antibiotics appropriately.